PENGARUH LATIHAN 100-YARD SPRINT TERHADAP WAKTU REAKSI PADA TIM FUTSAL PENDIDIKAN KEPELATIHAN OLAHRAGA ANGKATAN 2010 UNIVERSITAS RIAU - Fitriani '; Ramadi '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The issues raised in this study is " What is the effect of exercise 100-Yard Sprint To Reaction time In Futsal Team Player Sport Coaching Education Force 2010 University of Riau?". This research is experimental research that aims to find out the effect of exercise 100-yard sprint toward reaction time In Futsal Team Player Sport Coaching Education Force 2010 University of Riau. The population is Player Sport Coaching Education Force 2010 University of Riau as many as 10 people.This study uses total sampling technique the entire population sampled. Based on the determination of sample, the sampel of 10 people. As the independent variable (x) was training 100-yard sprints while the dependent variable (y) is the agility. Were obtained and collected through the initial test and final test before and after exercise 100-yard sprint using a meansuring tool that is reaction timer  test. The method of processing data using descriptive statistics calculations and to test the hypothesis using the t test. The hypothesis proposed in this study is the effect of exercise 100-yard sprint to ward reaction time In Futsal Team Player Sport Coaching Education Force 2010 University of Riau.The results of the t test produced 7,65 and 1,833 t table at the significant level of 0.05. Means ttest> t table. It can be concluded that H0 is greater than the Ha. So,  the conclusion is there is a significant effect of exercise 100-yard sprint to ward reaction time Futsal Team Player Sport Coaching Education Force 2010 University of Riau. Key Words: Exercise 100-yard  sprint. Reaction Time